IMPROVING STRATEGIES OF LEARNING ENGLISH IN HIGHER EDUCATION - Kosimova Kumush Golib kizi (Journal of new century innovations, 2024)
Abstract: This study aims to identify the current scenario and the reasons behind these challenges. This article also shows students some ways to develop writing skills that they can apply in their academic lives. Data were collected using a variety of writing processes and a student-structured questionnaire based on classroom activities. The survey was conducted among students studying in the English language department of private higher educational institutions in Uzbekistan or taking language courses. Based on the results, some practical recommendations were made for all three stakeholders: students, teachers and institutions.